Analysis of the economic impact of climate change and climate change adaptation strategies for fisheries sector in Pacific coral triangle countries: Model, estimation strategy, and baseline results. (May 2016) - Dey, Madan Mohan; Rosegrant, Mark W.; Gosh, Kamal; Chen, Oai Li; Valmonte-Santos, Rowena
Abstract: This paper presents a supply-and-demand model for the fisheries sector developed to assess the effect of climate change and related adaptation strategies in four Pacific coral triangle (CT) countries—Fiji, Solomon Islands, Timor-Leste, and Vanuatu. The modeling approach used in this paper represents climate change in terms of supply shocks, and works out its economic consequences using the microeconomic tools of supply and demand. The analysis has considered three time periods: current (represented by the average data of the three most recent available years 2006–2009), medium term (2035), and long term (2050). The study covers all fisheries and aquaculture species, grouped into six key subsectors: tuna, other oceanic finfish, coastal finfish, coastal invertebrates, freshwater finfish, and freshwater invertebrates. Results of the baseline model indicate that with rising per capita income and population, fish demand is expected to increase substantially up to 2050. In contrast to significant growth in fish demand, growth in domestic fish production is projected to be slow due to climate change and other constraints. There is a strong likelihood that many Pacific countries will become large net importers of fish under the baseline scenario (i.e., without implementing climate change adaptation strategies). Likewise, per capita consumption of domestically produced fish is projected to decline under the baseline scenario. Highlights: Developed and used supply-and-demand models for fisheries sector in Pacific countries. Reported baseline results and assessed effect of climate change in four Pacific countries. Seafood demand in Pacific countries will increase substantially for the period up to 2050. Supply of fish from coastal fisheries will decline due to climate change.